2008
DOI: 10.1021/cg701227n
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Al-Doped Single-Crystalline 6H-SiC Nanowires

Abstract: We report for the first time the synthesis of Al-doped 6H-SiC nanowires with high yield and high quality. The nanowires were obtained by the catalyst-assisted pyrolysis of polymeric precursors with FeCl2 as the catalyst. The doping concentrations were controlled by tailoring the Al concentrations in the precursors. It was observed that the Al dopants caused red-shifts of the photoluminescence bands. The results suggest a simple technique to synthesize Al-doped SiC nanomaterials in a controlled manner. The obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 47 publications
3
55
1
Order By: Relevance
“…The authors have compared the spectrum with the corresponding one of bulk 6H-SiC and they have concluded that, the lattice parameters of the nanowires decrease without mentioning any quantitative result. The same conclusion has been obtained in [43], although the change in angle was of the order of 0.1º. This is attributed to a large incorporation of the big Al ions in substitutional sites of SiC resulting in a strained crystal and in a lattice constant change.…”
Section: X-rays Diffraction (Xrd)supporting
confidence: 81%
See 4 more Smart Citations
“…The authors have compared the spectrum with the corresponding one of bulk 6H-SiC and they have concluded that, the lattice parameters of the nanowires decrease without mentioning any quantitative result. The same conclusion has been obtained in [43], although the change in angle was of the order of 0.1º. This is attributed to a large incorporation of the big Al ions in substitutional sites of SiC resulting in a strained crystal and in a lattice constant change.…”
Section: X-rays Diffraction (Xrd)supporting
confidence: 81%
“…The diameters of the NWs thin ends are about 10-30 nm, while their thick ends range from tens of nanometers to more than 100 nm, depending on their lengths (maximum 1 μm). In a subsequent study, Gao et al [43] reported the synthesis of Al-doped 6H-SiC, [10 1 2 ]-oriented, nanowires 150-300 nm in diameter by catalyst-assisted (FeCl 2 ) pyrolysis of polymeric precursors. Wei et al [44] succeeded also to obtain 6H-SiC, [10 1 0 ]-oriented, NWs but with a lower diameter of 5-200 nm and a length of tens to hundreds of micrometers by using microwave heating of a xerogel containing Si and C precursors as well as nano-Al powders.…”
Section: H-sic Nw Formationmentioning
confidence: 99%
See 3 more Smart Citations